2016
DOI: 10.1007/s10676-016-9404-2
|View full text |Cite
|
Sign up to set email alerts
|

The development of assistive dementia technology that accounts for the values of those affected by its use

Abstract: Developing technology that accounts for values has been achieved in many areas, including security, gaming, finance, engineering, and many more. The main methodological approach has been that of value sensitive design. But most of the work to date has been on the first of its three stages. The focus of this article is on advances related to its second stage, empirical investigation, and in particular the impact of contextual understanding in that stage. Although lessons can be learnt from other domains, the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
(49 reference statements)
0
33
0
Order By: Relevance
“…It is generally assumed that there is a single, fixed meaning to autonomy, at least in any given context, and that preservation of autonomy simply requires, at most, identification of the correct version (Manders-Huits 2011). Some have noted the meaning of autonomy can vary with different contexts (Burmeister 2016), but it is possible that it only appears the meaning has changed because the difficulties perceived apply to one version of autonomy and not others, thus making the problematic version of autonomy obvious. Our review of ETICA's survey of threats to autonomy has revealed that many versions of autonomy may be applicable within the one context, some of which may have problems while others do not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally assumed that there is a single, fixed meaning to autonomy, at least in any given context, and that preservation of autonomy simply requires, at most, identification of the correct version (Manders-Huits 2011). Some have noted the meaning of autonomy can vary with different contexts (Burmeister 2016), but it is possible that it only appears the meaning has changed because the difficulties perceived apply to one version of autonomy and not others, thus making the problematic version of autonomy obvious. Our review of ETICA's survey of threats to autonomy has revealed that many versions of autonomy may be applicable within the one context, some of which may have problems while others do not.…”
Section: Discussionmentioning
confidence: 99%
“…: playing sport or music) or healthy reflexes, which can also express personal autonomy (Meyers 2005(Meyers , 1989. These issues collide with particular urgency where ICT's become concerned with care for the ill or aged (Agich 2003;Burmeister 2016;Dworkin 1988), but also wherever ICT's come to mediate what someone considers to be core elements of their life.…”
Section: Autonomymentioning
confidence: 99%
“…All three investigation types are interdependent and inform each other (Manders-Huits 2011). Burmeister (2016) shows how an identified value can be refined by empirical insights, which support its in-depth conceptualization and understanding. Due to the interdependency of the three investigations, we consider iterations between them as an important cornerstone of the VSD tripartite methodology.…”
Section: Introductionmentioning
confidence: 89%
“…Much of my own work has been to do with technology use by people with cognitively diminished capacity (Burmeister, 2010(Burmeister, , 2016Pakrasi, Burmeister, McCallum, Coppola, & Loeb, 2015;Teipel et al, 2016), and I wish to use that as an example of the need to look beyond past work alone. For instance, Najaftorkaman et al (p. 584) looked at the effects of computer literacy on EMR adoption, but in so doing did not consider the EMR needs of people whose cognitive limitations make such literary competence difficult to achieve.…”
mentioning
confidence: 99%
“…However, what about the autonomy of the client? Current state of the art in regards to assistive technology for people with dementia attempts to maximize autonomy, while ensuring safety, such that technology assistants do not take over complete function, but facilitate as much as possible the use of the user's remaining cognitive function (Burmeister, 2016;Teipel et al, 2016).…”
mentioning
confidence: 99%